Application of Some Carbon Fabrics as Outstanding Supercapacitor Electrode Materials in Acetonitrile Based Electrolyte. Issue 2 (12th January 2017) - Palm, Rasmus; Kurig, Heisi; Romann, Tavo; Joost, Urmas; Kanarbik, Rait; Väli, Ronald; Tallo, Indrek; Thomberg, Thomas; Jänes, Alar; Lust, Enn
Abstract : Different carbon fabrics have been investigated as electrodes for supercapacitors by cyclic voltammetry, electrochemical impedance spectroscopy and by lifetime test method under constant cell potential in 1 M triethylmethylammonium tetrafluoroborate solution in acetonitrile. High capacitance (110 F g −1 ), power and energy densities (75 kW kg −1 and 28 Wh kg −1, respectively) have been achieved. Comparison of data with high-performance titanium carbide-derived carbon electrodes has been made. The carbon fabric with high specific surface area (1130 m 2 g −1 ), small pores (width < 2 nm) and with lowest Si and oxygen functionalities demonstrated the best performance. The electrochemical impedance spectroscopy and cyclic voltammetry measurements showed nearly ideal capacitive behavior up to cell potential 2.8 V. However, during the lifetime tests the system degrades slowly (even at 2.7 V), which is probably caused by slow faradaic reactions seen at higher cell potentials (≥3.0 V).